Adaptation of Lymnaea fuscus and Radix balthica to Fasciola hepatica through the experimental infection of several successive snail generations - Rondelaud, Daniel (BioMed Central, 2014)
BACKGROUND: High prevalence of Fasciola hepatica infection (>70%) was noted during several outbreaks before the 2000s in several French farms where Galba truncatula is lacking. Other lymnaeids such as Lymnaea fuscus, L. glabra and/or Radix balthica are living in meadows around these farms but only juvenile snails can sustain complete larval development of F. hepatica while older snails were resistant. The low prevalence of infection (<20%) and limited cercarial production (<50 cercariae per infected snail) noted with these juveniles could not explain the high values noted in these cattle herds. As paramphistomosis due to Calicophoron daubneyi was not still noted in these farms, the existence of another mode of infection was hypothesized. Experimental infection of several successive generations of L. glabra, originating from eggs laid by their parents already infected with this parasite resulted in a progressive increase in prevalence of snail infection and the number of shed cercariae. The aim of this paper was to determine if this mode of snail infection was specific to L. glabra, or it might occur in other lymnaeid species such as L. fuscus and R. balthica. METHODS: Five successive generations of L. fuscus and R. balthica were subjected to individual bimiracidial infections in the laboratory. Resulting rediae and cercariae in the first four generations were counted after snail dissection at day 50 p.e. (20°C), while the dynamics of cercarial shedding was followed in the F5 generation. RESULTS: In the first experiment, prevalence and intensity of F. hepatica infection in snails progressively increased from the F1 (R. balthica) or F2 (L. fuscus) generation. In the second experiment, the prevalence of F. hepatica infection and the number of shed cercariae were significantly lower in L. fuscus and R. balthica (without significant differences between both lymnaeids) than in G. truncatula. CONCLUSION: The F. hepatica infection of several successive snail generations, coming from parents infected with this parasite, resulted in a progressive increase in prevalence and intensity of snail infection. This may explain high prevalence of fasciolosis noted in several cattle-breeding farms when the common snail host of this digenean, G. truncatula, is lacking.